2004
DOI: 10.1192/bjp.184.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric complications in patients with severe acute respiratory syndrome (SARS) during the acute treatment phase: a series of 10 cases

Abstract: In February 2003, Hong Kong was hit by a community-wide outbreak of severe acute respiratory syndrome (SARS). During the period of the outbreak, 10 patients with SARS with psychiatric complications were referred to our Consultation and Liaison Psychiatry Team for assessment and management. We found that both the direct and indirect effects of SARS such as symptom severity, total isolation during treatment and administration of steroid were probable causes of psychiatric complications. In this paper, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(149 citation statements)
references
References 4 publications
7
136
0
6
Order By: Relevance
“…The results are not surprising as, in addition to the physical impairment, the long period of isolation and extreme uncertainty during the SARS illness had created enormous psychological stress 57 and mood distur-bances. 58 In addition, steroid toxicity, personal vulnerability, and psychosocial stressors might have jointly contributed to the development of psychosis in some patients. 59 Other studies 11-14 on acute lung injury or ARDS survivors unrelated to SARS have reported impaired health status at 1 to 5 years after recovery, whereas pulmonary function abnormalities, especially Dlco, correlated with SF-36 domains.…”
Section: Discussionmentioning
confidence: 99%
“…The results are not surprising as, in addition to the physical impairment, the long period of isolation and extreme uncertainty during the SARS illness had created enormous psychological stress 57 and mood distur-bances. 58 In addition, steroid toxicity, personal vulnerability, and psychosocial stressors might have jointly contributed to the development of psychosis in some patients. 59 Other studies 11-14 on acute lung injury or ARDS survivors unrelated to SARS have reported impaired health status at 1 to 5 years after recovery, whereas pulmonary function abnormalities, especially Dlco, correlated with SF-36 domains.…”
Section: Discussionmentioning
confidence: 99%
“…To encourage reply we gave phone call to all patients before sending them questionnaires. One of the questionnaires, the SARS Neuropsychiatric Symptoms Checklist (NPSC), was specifically designed to evaluate the neuropsychiatric complaints after SARS according to our initial experiences [5]. It consisted of 25 items covering six neuropsychiatric domains of interest (see Appendix for questionnaire), namely cognition (Q1-4), mania (Q5-8), depression (Q9-15), anxiety (Q16-18), psychosis (Q19-21) and behavioural symptoms (Q22-25).…”
Section: Survey Methodsmentioning
confidence: 99%
“…In the immediate aftermath of the SARS epidemic, psychiatric morbidity of individual patients began to emerge. The main problems involved adjustment reactions with increased anxiety levels [4][5][6][7]. Studies showed that 10-35% of SARS survivors reported having features of anxiety, depression or both during the early recovery phase [3,8,9].…”
Section: Introductionmentioning
confidence: 99%